Assessing Vulnerability and Resilience in the Face of Climate Change: A Case Study of North - East India - Singha, Sutandra (European Journal of Sustainable Development, 2018)
The North Eastern Region (NER) possesses ecological and strategic significance for India. Hence, socio- economic stability of the region is of utmost importance. However, the NER is critical from the climate change perspective due to the majority of the rural population and the economy based on natural resources and climate-sensitive sectors - agriculture, water resource, and forestry. The region is not properly equipped to handle the adversities of climate change impacts. Analysis of climate change impacts and vulnerabilities at the state level of North-East India is, therefore, necessary to develop adaptation strategies. In this backdrop, the present study assesses the climate change vulnerability of eight North-Eastern states - Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim, and Tripura to climate change impacts, using the Vulnerability-Resilience Indicators Model (VRIM after Moss et al. 2001). For this purpose, proxies have identified and used for various sectors of climate sensitivities and coping-adaptive capacity. The outcome has analyzed at the state level regarding relating the values of VRIM with the respective socio-economic situation to find out the sources of vulnerability. This methodological framework will help policymakers, analysts and stakeholders to systematically evaluate individual as well as sets of indicators to identify the vulnerable areas and sectors. Concluding section of this study offers some practical policy measures that would substantially reduce vulnerability to climate change and improve long-term resilience in the NER. Keywords: Climate Change, Coping-Adaptive Capacity, North Eastern Region, Sensitivities, Vulnerability- Resilience Indicators Model